GE_GERICHTE A/4471/2017 vom 3. Mai 2018 - GE Cour de justice (2018)
Péremption de la poursuite Changement de créancier Plaideur téméraire Opposition tardive | LP.88.al2; LP.77; LP.20a.al2.ch5; LP.32.al2